Infrastructure and Resource Assistance to Improve Educational Facilities at MT-TPA-MDT Hidyatussibiyan - Supini; Hidayah, Nur Laeli; Mohamad Pailin; Wawan H; Anggun Fadilah; Dedi Sutiadi; Rizky Mubarok; Hendra; Edwin; Sahdid Sainaro; Nurdin Zaenali (PT FORMOSA CENDEKIA GLOBAL, 2024)
Improving the quality of education in non-formal educational institutions such as Madrasah Tsanawiyah-Taman Pendidikan Al-Qur'an-Madrasah Diniyah Takmiliyah (MT-TPA-MDT) is highly dependent on the availability of adequate infrastructure and effective resources. This study aims to evaluate efforts to provide infrastructure and resource assistance that can improve educational facilities at MT-TPA-MDT Hidyatussibiyan. The method used in this community service is a participatory approach through providing assistance in the form of classroom renovation, provision of learning aids, and training for teachers and madrasah managers. The results of this program show a significant increase in the quality of the teaching and learning process and student motivation, as reflected in the level of attendance and active participation during learning activities. This program is expected to be a model for the development of educational facilities in other madrasahs.